2020
DOI: 10.3390/w13010048
|View full text |Cite
|
Sign up to set email alerts
|

Performances of Sheet-Pipe Typed Subsurface Drainage on Land and Water Productivity of Paddy Fields in Indonesia

Abstract: Subsurface drainage technology may offer a useful option in improving crop productivity by preventing water-logging in poor drainage paddy fields. The present study compared two paddy fields with and without sheet-pipe type subsurface drainage on land and water productivities in Indonesia. Sheet-pipe typed is perforated plastic sheets with a hole diameter of 2 mm and made from high-density polyethylene. It is commonly installed 30–50 cm below the soil surface and placed horizontally by a machine called a mole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
9
0
2
Order By: Relevance
“…Commonly, the lower the actual evapotranspiration, the lower the yield [18,60], according to the basic equation reported by van Lier et al [61]. However, several experiments showed different results [10,[62][63][64]. It seems there is an inconsistent correlation between crop coefficient and grain yield.…”
Section: Discussionmentioning
confidence: 98%
“…Commonly, the lower the actual evapotranspiration, the lower the yield [18,60], according to the basic equation reported by van Lier et al [61]. However, several experiments showed different results [10,[62][63][64]. It seems there is an inconsistent correlation between crop coefficient and grain yield.…”
Section: Discussionmentioning
confidence: 98%
“…In the same field, the evaluation of the sheet-pipe system on the crop productivity was conducted based on the field investigation from 5 May to 6 August, 2018 as one rice season. At the SP-area, the grain yield with more than 13.36% was confirmed [12].…”
Section: A Case Study On the Drainage By Using The Sheet-pipe Systemmentioning
confidence: 85%
“…The first application of the sheet-pipe system was performed at the Indonesian Center for Rice Research, Sukamandi, West Java, Indonesia in 2018 as a pilot project [12,14]. The tested site is a paddy field with an area of 10,000 m 2 and the field was divided into two areas (i.e., as a sheet pipe installed area (SP-area) and non sheet pipe area (NSP-area)).…”
Section: A Case Study On the Drainage By Using The Sheet-pipe Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Research showed that land with sheet pipe could increase the production up to 13% in a single trial of one rice planting season [4] although evapotranspiration was lower because the water level was maintained below the surface. For one year with rice-paddy-soybean and rice-paddy-paddy cropping patterns, the yield increased by 11.54% and 26.94% [5], respectively.…”
Section: Introductionmentioning
confidence: 99%